2007
DOI: 10.1007/s00701-007-1115-7
|View full text |Cite
|
Sign up to set email alerts
|

Cervical arthroplasty in a patient with Klippel-Feil syndrome

Abstract: SummaryThis is the first published report of a patient with KlippelFeil syndrome treated with cervical arthroplasty. A 36-year-old man presented with posterior neck pain and myelopathic symptoms. A radiograph demonstrated congenital fusion of the vertebral bodies at C2-3, C4-5 and C5-6. On MRI, the spinal cord was compressed by a protruding cervical disc and bony spurs at C6-7. After anterior discectomy and decompression of the spinal cord at the C6-7 level, the disc was replaced with the Bryan cervical disc s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Two case reports of disc replacement performed adjacent to congenitally-fused motion segments because of Klippel-Feil syndrome noted improved symptoms with retained disc motion after arthroplasty. 38,39 In another case study, Sekhon reported good results after a 2-level cervical TDR (at C4 -C5 and C7-T1) adjacent to a prior 2-level ACDF at 7-month follow-up. 40 In the current study, the PCM device was able to restore motion at the operated adjacent level.…”
Section: Discussionmentioning
confidence: 96%
“…Two case reports of disc replacement performed adjacent to congenitally-fused motion segments because of Klippel-Feil syndrome noted improved symptoms with retained disc motion after arthroplasty. 38,39 In another case study, Sekhon reported good results after a 2-level cervical TDR (at C4 -C5 and C7-T1) adjacent to a prior 2-level ACDF at 7-month follow-up. 40 In the current study, the PCM device was able to restore motion at the operated adjacent level.…”
Section: Discussionmentioning
confidence: 96%
“…14 For example, a 36-year-old man with KF presented after a motor vehicle accident with neck pain, tingling, and motor weakness of his left forearm, mildly increased deep tendon reflexes, and ankle clonus. 15 The only joints in the cervical spine that were not congenitally fused were C3/4 and C6/7, of which both levels demonstrated significant stenosis. The patient was treated surgically with symptom resolution except for mild posterior neck pain.…”
Section: Discussionmentioning
confidence: 96%
“…implanted the Bryan artificial disc at C4/5 level and good short-term results were encountered. In another case report, Yi et al 17. performed a C6-7 arthroplasty and preservation of motion was maintained at 2 years after surgery.…”
Section: Discussionmentioning
confidence: 99%